Mutasyabihat Hadith According Ibn Hajar al-â€˜Asqalani in His Fath al-Bariy Syarh Shahih al-Bukhariy (Study of Understanding of Hadith) - Munawar, Ali Mahfuz; Marhumah, Marhumah; Haris, Abdul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
â€œAyat MutasyÄbihÄtâ€ studies are often discussed differently from â€œHadith MutasyÄbihÄtâ€ studies â€œHadith MutasyÄbihÄtâ€ are traditions that are not yet clear in meaning and purpose because they contain a variety of meanings, so there is a need for in-depth research in order to obtain the proper meaning. The traditions that are said to be mutasyÄbihÄt are traditions that enter into indicators, traditions pronounced by the Prophet symbolically, traditions found improbable in their eyes, traditions that are illogical or logical and metaphysical traditions or unknown meanings such as the afterlife, heaven, hell, the attributes of God, the torment of the grave and the apocalypse. This research will specialize the â€œhadits mutasyÄbihÄtâ€ which explains the nature of Allah by using the method of matan criticism and the understanding of hadith, from this study found differences of opinion in understanding the â€œhadith mutasyÄbihÄtâ€ there are those who reject â€œtakwilâ€ and those who preach their meanings by not reducing the majesty of God.